Kontribusi Komponen Kebugaran Fisik terhadap Akurasi Pukulan Smash Bola Voli pada Mahasiswa Pendidikan Jasmani Universitas Pamulang - Muhardiyanti, Mutia; Jaya, Hendra; Khoerunnisa, Dinda (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2026)
The accuracy of smash in volleyball is influenced by various components of physical fitness, but the specific contribution of each component to physical education students has not been widely studied. This study aims to identify the contribution of leg muscle explosiveness, eye-hand coordination, and agility to the accuracy of volleyball smash. The research uses a correlational quantitative approach involving forty students of the Physical Education Study Program, Pamulang University who were selected through purposive sampling. Data collection was carried out through a vertical jump test, a ball throw to a wall test, an Illinois agility test, and a validated smash accuracy test. The data was analyzed using simple regression analysis and multiple regression with a significance level of five percent. The results showed that the explosiveness of the leg muscles contributed 55.1%, eye-hand coordination 66.6%, and agility 38.8% to the accuracy of the smash. Simultaneously, all three components contribute 77.1% to the accuracy of volleyball smash. Hand-eye coordination proved to be the most dominant predictor. These findings provide practical implications for the design of exercise programs that focus on developing physical fitness components holistically to optimize the smash abilities of physical education students.